Who Recovers Independent Bowel Management During the First Year After a Traumatic Spinal Cord Injury?: A Case-Control Study. (3rd April 2022) - Dionne, Antoine; Mac-Thiong, Jean-Marc; Lim, Victor; Richard-Denis, Andréane
Abstract : Objectives: The aims of the study were (1) to document the characteristics of patients with impaired bowel functioning during the subacute and chronic phases and (2) to identify factors associated with recovery of independent bowel functioning during the first year after traumatic spinal cord injury in patients who present impaired bowel functioning during the subacute phase, when bowel rehabilitation is completed. Design: This is a case-control study on 123 adult traumatic spinal cord injury patients. Bowel function assessments using item 7 of the Spinal Cord Independence Measure III were obtained 3 mos after traumatic spinal cord injury and during the early chronic phase. Univariate and multivariate analyses were conducted to identify predictors associated with recovery of independent bowel functioning between the initial assessment and follow-up. Results: Of the 110 patients available for analysis, 54 (49%) displayed impaired bowel functioning 3 mos after traumatic spinal cord injury. Of these, 19 (35%) recovered independent bowel functioning over the following 9 mos. The total motor score was the only significant predictor of this outcome. A total motor score lower than 42 was 100% predictive of absence of recovery. Conclusions: Recovering independent bowel management 1 yr after traumatic spinal cord injury was possible in 35% of patients despite impaired bowel functioning during the subacute phase. The total motor score measured 3 mos after injury could be useful for prognosticating potential for bowel functioning recovery because patients with total motor score lower than 42 are unlikely to recover. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) Demonstrate a comprehensive understanding of the course of recovery of independent bowel function after traumatic spinal cord injury; (2) Describe the vulnerable subset of patients who present impaired bowel function at 3 mos after injury despite having received specialized bowel rehabilitation; and (3) Predict with improved accuracy the level of bowel function reached in the chronic phase for patients who present with impaired bowel function at 3 mos after injury. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity.